2018
DOI: 10.1016/j.enbuild.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Developing a design framework to facilitate adaptive behaviours

Abstract: Adaptive behaviour has a significant impact on the quality of indoor environment, comfort, and energy consumption. Therefore, facilitating positive occupant behaviours will improve these three factors. The aim of this paper is to develop a design framework that can be used as part of the design process to facilitate adaptive behaviours.This paper reviews studies that focus on reasons behind adaptive behaviours, and implication of these adaptive behaviours on the built environment. This paper highlights that 'C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 150 publications
0
32
0
2
Order By: Relevance
“…It is shown that large openings can be used for still summer days and small high-level openings can be used for winter days to avoid overheating [50,69]. Windows at different levels (high and low-level openings) and sizes (small and large) can provide IAQ [15,20,50,[69][70][71] during both heating and non-heating seasons. Therefore, classrooms with windows at different levels and sizes can potentially increase occupants' practice of ABs.…”
Section: Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that large openings can be used for still summer days and small high-level openings can be used for winter days to avoid overheating [50,69]. Windows at different levels (high and low-level openings) and sizes (small and large) can provide IAQ [15,20,50,[69][70][71] during both heating and non-heating seasons. Therefore, classrooms with windows at different levels and sizes can potentially increase occupants' practice of ABs.…”
Section: Windowsmentioning
confidence: 99%
“…IAQ in classrooms is mainly assessed by CO2 levels [14][15][16][17][18], especially in buildings where people, exhaled air or bioeffluents are the main pollution sources [19]. Authors have previously suggested [20] that the main factors influencing IAQ in buildings fall into three categories of Context, Occupant and Building (COB).…”
Section: Introductionmentioning
confidence: 99%
“…Human behaviour is complex and varied, and it may not be perfectly represented in a statistical model. However, with a better understanding of it, it is hoped to optimize designs and use of the built environment [92][93][94].…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Nicol e Humphreys (2002) ilustram que as pessoas com mais oportunidades de adaptação terão menor probabilidade de sofrer desconforto. Geralmente, níveis mais altos de conforto e satisfação são observados quando os controles fornecem a possibilidade de operações eficientes, fáceis, intuitivas e acessíveis aos ocupantes e quando estes podem adotar comportamentos adaptativos, explicam Korsavi et al (2018).…”
Section: Edifícios Inteligentes E Verdes E Os Comportamentos Adaptativosunclassified
“…O edifício carece, segundo Cole (2008), de mudança no conceito do ocupante como receptor passivo, para usuário ativo que possa intervir no ambiente de forma a atingir os níveis de conforto esperado. Neste sentido, a APO (Avaliação Pós-Ocupação) é necessária, segundo Korsavi et al (2018), para descobrir como os ocupantes interagem com os controles, em que sequência adotam comportamentos adaptativos e para prever como os comportamentos afetam os fatores de qualidade interior, conforto e o consumo de energia.…”
Section: Edifícios Inteligentes E Verdes E a Apo (Avaliação Pós-ocupaunclassified